Wawasan Al-Qur’an Tentang Kekafiran - Muhammad Hariyadi; Lukman Nurhakim (LP2M Universitas PTIQ Jakarta, 2016)
Kafir (Infidel) is an open term that is specifically intended for people who do not get the guidance of Allah, disobeying Him, and does not recognize Allah as his God. The concept of disbelief is essentially a concept that has wide and stratified branches, not only of the people who are outside of Islam, but can be on the Muslims people even at the level of “disbelief” that light, so that someone who has blamed to be disbelief by others, does not automatically apply the law of infidels for himself and not directly come out from Islam, but it must go through a long and detail process on the court because the trial judge was entitled to determine the legal status of one’s disbelief. This paper reveal the meaning of kafirin various derivation, its meaning and contents so that the concept of infidelity can be placed proportionally, and one can distinguish kafirdiscourse theoretically and practically. In reality, kafirtheoretically does not so worried on us, but, to be blamed as kafir practically often a scourge to society, because of the severity of the consequences that a person receives after he declared as infidels.